UJI AKTIVITAS ENZIM PENISLIN G ASILASE (PGA) SECARA KUALITATIF TERHADAP ISOLAT Escherichia coli YANG BERASAL DARI AIR SUNGAI DI KOTA PADANG - MEGAHATI S.Si, M.Si, RUTH RIZE PAAS (STKIP PGRI Sumatera Barat, 2012)
Penicillin G acylase is catalysed hydrolisis enzym penicillin G to 6-amino penicilanad acid (6-APA). 6-APA is precursor to made semisintheticpenicillin. Semisynthetic penicillin derivated of natural penicillin that get it bychange natural penicillin chemistry structure or sinthesis nuclear penicillin.Penicillin G acylase (PGA) produce of bacteria but bacteria produced numberpenicillin is limited so looking new bacteria penicillin produce is importen to do.Based it haved bacteria isolation in Padang town any rivers, include air batangKandis, air batang Kurao, air batang Kuranji, air batang Arau dan air batang Arudi kota Padang. This research do in Kopertis wilayah X laboratory. Activity assayPGA used Meevootisom methode is metode easy to selection, rapid and spesifikto selection bacteria strain PGA produced. Meevootisoom metode used Serratiamarsescens, is resisten to penicillin and sensitiv to 6-APA. Result of this researchis every isolated from all rivers contain PGA.